The ALPHA Project: Establishing consensus and prioritisation of global community recommendations to address major challenges in lupus diagnosis, care, treatment and research - Kenneth Kalunian; Susan Manzi; Amy H Kao; Eric F Morand; Brad H Rovin; Karen H Costenbader; Karin Tse; Laura Eve Schanberg; Yaritza Peña; Kathleen Arntsen; Kenneth Getz; Joan M Von Feldt; et al. (Lupus Science and Medicine, 2021)
The Addressing Lupus Pillars for Health Advancement (ALPHA) Project is a global consensus effort to identify, prioritise and address top barriers in lupus impacting diagnosis, care, treatment and research. To conduct this process, the ALPHA Project convened a multistakeholder Global Advisory Committee (GAC) of lupus experts and collected input from global audiences, including patients. In phase I, the ALPHA Project used expert interviews and a global survey of lupus experts to identify and categorise barriers into three overarching pillars: drug development, clinical care and access to care. In phase II, reported here, the GAC developed recommended actionable solutions to address these previously identified barriers through an in-person stakeholder meeting, followed by a two-round scoring process. Recommendations were assessed for feasibility, impact and timeline for implementation (FIT), where potential FIT component values were between 1 and 3 and total scores were between 3 and 9. Higher scores represented higher achievability based on the composite of the three criteria. Simplifying and standardising outcomes measures, including steroid sparing as an outcome (drug development) and defining the lupus spectrum (clinical care) ranked as the highest two priority solutions during the GAC meeting and received high FIT scores (7.67 and 7.44, respectively). Leveraging social media (access to care) received the highest FIT score across all pillars (7.86). Cross-cutting themes of many solutions include leveraging digital technology and applying specific considerations for special populations, including paediatrics. Implementing the recommendations to address key barriers to drug development, clinical care and access to care is essential to improving the quality of life of adults and children with lupus. Multistakeholder collaboration and guidance across existing efforts globally is warranted.